2018
DOI: 10.1111/ans.14360
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal prostate biopsy sepsis rate following reduced quinolone antibiotic prophylaxis from six doses to single dose

Abstract: Our study supports the use of a single dose of ciprofloxacin as sufficient antibiotic prophylaxis prior to TRPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The duration of pre-biopsy fluoroquinolone prophylaxis appears unrelated to infection risk. Bangash and colleagues performed a prospective analysis of post-biopsy infection rates in 2018, and suggested that a single dose of ciprofloxacin 500 mg was non-inferior to a three-day course of twice daily ciprofloxacin in over 700 patients (31).…”
Section: Post-trus Biopsy Infection and Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of pre-biopsy fluoroquinolone prophylaxis appears unrelated to infection risk. Bangash and colleagues performed a prospective analysis of post-biopsy infection rates in 2018, and suggested that a single dose of ciprofloxacin 500 mg was non-inferior to a three-day course of twice daily ciprofloxacin in over 700 patients (31).…”
Section: Post-trus Biopsy Infection and Sepsismentioning
confidence: 99%
“…In 80 high-risk patients who received ertapenem, there were no cases of sepsis compared to a rate of 6.7% within the cohort who received ciprofloxacin and amoxicillin-clavulanate (35). In several Australian studies, carbapenem use has been associated with a zero-sepsis rate (31,36). Despite the apparent reduction in TRUS biopsy related infection, the use of carbapenems should be minimised where possible due to the threat of Enterobacteriaceae carbapenemresistance.…”
Section: Carbapenem Prophylaxismentioning
confidence: 99%
“…The risk of infection complicating TRUS prostate biopsies is reduced with appropriate antibiotic prophylaxis 18 . We have previously reported the comparison of infective complication rates following the change in the prophylactic antibiotic regimen, 19 now updated to include all men (876 out of 1000) who had a TRUS prostate biopsy. The increase in infective complications was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%